Silicon-Mediated Priming Induces Acclimation to Mild Water-Deficit Stress by Altering Physio-Biochemical Attributes in Wheat Plants - Hameed, Arruje; Farooq, Tahir; Hameed, Amjad; Sheikh, Munir Ahmad (Frontiers in Plant Science, 2021)
Water-deficit stress negatively affects seed germination, seedling development, and plant growth by disrupting cellular and metabolic functions, reducing the productivity and yield of field crops. In this study, sodium silicate (SS) has been employed as a seed priming agent for acclimation to mild water-deficit stress by invoking priming memory in wheat plants. In pot experiments, the SS-primed (20, 40, and 60 mM) and non-primed control seeds were allowed to grow under normal and mild water-deficit conditions. Subsequently, known methods were followed for physiological and biochemical studies using flag leaves of 98-day mature wheat plants. The antioxidant and hydrolytic enzymes were upregulated, while proteins, reducing sugars, total sugars, and glycine betaine increased significantly in the flag leaves of wheat plants originated from SS-treated seeds compared to the control under mild water-deficit stress. Significant decreases in the malondialdehyde (MDA) and proline contents suggested a controlled production of reactive oxygen species, which resulted in enhanced cell membrane stability. The SS priming induced a significant enhancement in yield, plant biomass, and 100-grain weight of wheat plants under water-deficit stress. The improvement in the yield parameters indicated the induction of Si-mediated stress acclimation in SS-primed seeds that elicited water-deficit tolerance until the maturity of plants, ensuring sustainable productivity of climate-smart plants.